Morphological studies in lycopersicon esculentum Mill. lines in Southwestern Nigeria (2007)
Morphological studies of thirty lines of Lycopersicon esculentum Mill were carried out in order to find out characters, which may be used for the delimitation of the cultivars in Nigeria. The quantitative and qualitative characters studied include leaf type, leaf length, leaf shape, leaf breadth, petiole length, number of leaves per plant, number of leaflets per leaf, number of serration per leaflet days taken for germination, days taken for first picking, stem diameter, fruit diameter, fruit shape, fruit colour, stem type, stem colour, stem texture, leaf arrangement and growth habit. Morphological characters that indicate close affinity amongst the cultivars include leaf type, leaf base, leaf shape, leaf apex, leaf margin, leaf arrangement stem colour, fruit colour, number of calyx and corolla. However, the features that are taxonomically relevant in the delimitation of lines of L. esculentum are fruiting habit, fruit shape and presence or absence of ridges on the fruits. The three cultivars recognized are Ibadan local, hybrid and Roma VF. Numerical analysis of the qualitative and quantitative characters data using cluster analysis-average linkage, single linkage, complete linkage and centroid method delimit all the thirty lines into three major groups which conform to the results of the morphological analysis.